Nucleotide sequence and insertional inactivation of a Bacillus subtilis gene that affects cell division, sporulation, and temperature sensitivity. - Beall, B (1989)
Located at 135 degrees on the Bacillus subtilis genetic map are several genes suspected to be involved in cell division and sporulation. Previously isolated mutations mapping at 135 degrees include the tms-12 mutation and mutations in the B. subtilis homologs of the Escherichia coli cell division genes ftsA and ftsZ. Previously, we cloned and sequenced the B. subtilis ftsA and ftsZ genes that are present on an 11-kilobase-pair EcoRI fragment and found that the gene products and organization of these two genes are conserved between the two bacterial species. We have since found that the mutation in the temperature-sensitive filamenting tms-12 mutant maps upstream of the ftsA gene on the same 11-kilobase-pair EcoRI fragment in a gene we designated dds. Sequence analysis of the dds gene and four other open reading frames upstream of ftsA revealed no significant homology to other known genes. It was found that the dds gene is not absolutely essential for viability since the dds gene could be insertionally inactivated. The dds null mutants grew slowly, were filamentous, and exhibited a reduced level of sporulation. Additionally, these mutants were extremely temperature sensitive and were unable to form colonies at 37 degrees C. Another insertion, which resulted in the elimination of 103 C-terminal residues, resulted in a temperature-sensitive phenotype less severe than that in the dds null mutant and similar to that in the known tms-12 mutant. The tms-12 mutation was cloned and sequenced, revealing a nonsense codon that was predicted to result in an amber fragment that was about 65% of the wild-type size (elimination of 93 C-terminal residues).